“The Flower and the Wall”: Poet‐Activist Wiji Thukul and Progressive Martyrdom in Post‐Suharto Indonesia - Miller, Stephen L. (2024)
Since the fall of Major-General Suharto’s “New Order” regime, Indonesia has struggled to deal with its authoritarian legacy. This article argues that in the quarter of a century since his disappearance, the Indonesian poet-activist Wiji Thukul (1963–1998?) has become a martyr for the still unfulfilled progressive ideals of the Reformasi (reform) movement that helped to bring down that regime in 1998. Using the developing body of theory around “secular” or “political” martyrdom, this article examines the process by which this status has been achieved, situating its development alongside the emergence of the Refusing to Forget movement, as well as comparing and contrasting his fate with that of two other candidates for the label of Reformasi martyr: those of the labour activist Marsinah (1969–1993) and the human rights lawyer Munir Said Thalib (1965–2004). It argues that Thukul’s role as a martyr has been significant in maintaining progressive public discourse about the human rights abuses of the Suharto period, as well as the continuing illiberalism of the period since the end of the regime, and that Thukul remains relevant to efforts to stimulate and nurture the fragile democratisation project that was initiated in the late New Order period. In particular, the authors see Thukul’s brand of grassroots creative practice as playing a central role in his emergence as a progressive icon and in giving his life and work international significance.